Analysis of Cost and Revenue Structures of Palm Sugar Business in Ponre Waru Village, Wolo District, Kolaka Regency - Asriani, Asriani (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2020)
The purpose of this study was to determine: (1) to determine the cost structure of palm sugar business in Ponre Waru Village, Wolo District, Kolaka Regency, and (2) to determine the income of palm sugar business in Ponre Waru Village, Wolo District, Kolaka Regency. The population taken in this study were all owners of the palm sugar industry in Ponre Waru Village, Wolo District, Kolaka Regency, as many as 20 people. The research method used is the census method. The research analysis uses cost structure analysis, revenue, and income. The results showed that: (1) the structure of the palm sugar business costs with the highest value was the tapping cost of Rp.151,500. and the lowest cost is transportation cost, namely Rp. 105,000, and (2) the average palm sugar business income in Ponre Waru Village, Wolo District, Kolaka Regency is Rp. 1,947,850.